Does Artificial Intelligence Truly Democratize Healthcare Access? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2022)
The promise of Artificial Intelligence AI in medicine is often framed as a revolutionary force capable of transcending geographical, economic, and social bar...
Keywords: Diagnostics; Artificial Intelligence; Healthcare Innovation; Patient Care; Machine Learning